Effect of alternative polishing techniques on the roughness of acrylic resins - Meirelles Cogo, Deborah (2003)
ln the first part of this experiment, a chemical polishing technique for acrylic resins using a LG microwave oven model MB (315ml - 1.000watts) to heat the polishing fluids was sought. The microwave oven potency and the time required to heat the polishing fluids to a temperature of81 ± 5%C - temperature interval obtained in the electric polishing machine - was 900watts (90% of the maximum potency) and 90 seconds. Subsequently, a 100 prototypes were made, 50 samples of acrylic resin chemically activated and 50 samples of acrylic resin activated by microwave oven energy, which were submitted to 5 different polishing techniques: l) mechanical polishing - control group, 2) chemical polishing in electric polishing machine using polishing fluid., 3) chemical polishing in electric polishing machine using resin monomer, 4) chemical polishing in microwave oven using polishing fluid, 5) chemical polishing in microwave oven using resin monomer. They were compared using the effectiveness of the technique as a parameter for the superficial roughness of the acrylic resins. For this evaluation a rugosimeter S]-201 (Mitotoyo - ]apan) was used. The results were submitted to the analysis of variance and the means compared using the Tukey test (0= 1%). The results showed that ali polishing techniques promoted roughness values with statistical significative difference when compared to the mechanical polishing technique, which was below the R.,, threshold of 0,2 m, (a= 1%). There were no significant statistical differences among the four chemical polishing techniques.